Wet Air Oxidation (WAO) treament of wastewater from textile industries - Abu Hassan, Mohd. Ariffin (Faculty of Chemical and Natural Resource Engineering, 2008)
This research details an investigation o f the Wet Air Oxidation (WAO) of wastewater from textile industries in order to develop a method for treating these wastewaters. The objective of this WAO treatment is to produce an effluent that is more aerobically biodegradable than the initial textile wastewater. WAO experiments were conducted on textile wastewaters, quantifying the effect on increasing the WAO temperature (180 - 220°C) for two hours at oxygen pressure of 20 bars. It was found that a greater WAO temperature significantly increased the Total Organic Carbon (TOC), Chemical Oxygen Demand (COD) removals and turbidity reduction. A higher temperature gives a greater removal of TOC, COD and turbidity during the WAO o f textile wastewater. For instance, WAO resulted in almost 63%, 75% and 85% TOC removals after 120 min of oxidation at 180°C, 200°C and 220°C respectively, 65%, 75% and 89% COD removals at 180°C, 200°C and 220°C respectively and 72%, 80% and 94% turbidity reductions were achieved after 120 min of oxidation at 180°C, 200°C and 220°C respectively. Additionally TOC and COD were not completely destroyed at the conditions studied, indicating that there were organics that are refractory to further oxidation. Thus, there is always proportionally more residual TOC than COD, indicating that there was more partial oxidation (to residual organics) than total oxidation to CO2.